Music influences performance without increasing perceived exertion during high-intensity rowing intervals: a cross-over design study - Schittenhelm, Andrea; Brandt, Tom; Andres, Denny; Adler, Patrick; Fairhurst, Merle T.; Schmidt, Annette (Frontiers in Psychology, 2024)
Objectives This study assessed how exposure to slow (SBM) versus fast beat music (FBM) during high-intensity rowing intervals affects performance, heart rate (HR), lactate levels, relative perceived exertion (RPE), and recovery. Methods The A/B crossover design involved 21 participants performing 5 × 500 m rowing intervals under two conditions: FBM and SBM. Primary endpoint was the difference in total rowing time. Secondary endpoints included average HR, average RPE as well as rowing interval times, RPE, and HR per interval. For exploratory purpose, HR and lactate drop during the initial 5 min post completion was analyzed. Results Listening to FBM resulted in significantly shorter total rowing times (p = 0.009, rB = 0.59), especially during the 1st interval. The 1st interval was also significantly faster than intervals 2–5 (p < 0.001), with the greatest performance drop between the 1st and 2nd interval during FBM. Average HR was significantly lower when listening to SBM (p = 0.03, rB = 0.48), while average RPE showed no significant difference (p = 0.47, rB = 0.02). Lactate values after interval 5 were significantly lower in SBM (p = 0.05, rB = 0.41), but no significant difference was found for lactate drop (p = 0.21, rB = 0.21). However, participants exhibited a higher HR drop rate with SBM (p = 0.05, rB = 0.42). Conclusion FBM improved performance without increasing RPE, while SBM proved superior for recovery. Systematic customization of music based on intended training stimuli holds broad potential for the competitive sports, fitness, and health sector.